2023
DOI: 10.4103/jcn.jcn_87_22
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Validation of the Alexandria Retinopathy of Prematurity Model in Preterm Infants in Saudi Arabia

Abstract: Background: In developing countries, data on the applicability of existing models to predict retinopathy of prematurity (ROP) are scarce. The study aimed to validate the Alexandria ROP (Alex-ROP) and high-grade Alex-ROP (Hg Alex-ROP) models retrospectively to identify treatable ROP in a cohort of preterm infants in Saudi Arabia. Materials and Methods: We reviewed and included the records of 281 infants born prematurely in 2015–2021. We recorded the infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The possible mechanisms underlying the complications associated with RBC transfusions in preterm infants include increased incidence of oxidative injury secondary to the increase in iron levels or the release of inflammatory mediators from stored blood products. 35 The week 3 WG was a significant predictor, which was in accordance with another study conducted in Egypt, 36 which determined that WG at week 4 ( P < .001) followed by week 3 ( p = .003) were significantly lower in patients with type 1 ROP compared to patients with any-stage ROP or no ROP. Clinical studies demonstrated an association exists between an infant’s low serum IGF-1 and poor PWG and the risk of developing more severe ROP.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The possible mechanisms underlying the complications associated with RBC transfusions in preterm infants include increased incidence of oxidative injury secondary to the increase in iron levels or the release of inflammatory mediators from stored blood products. 35 The week 3 WG was a significant predictor, which was in accordance with another study conducted in Egypt, 36 which determined that WG at week 4 ( P < .001) followed by week 3 ( p = .003) were significantly lower in patients with type 1 ROP compared to patients with any-stage ROP or no ROP. Clinical studies demonstrated an association exists between an infant’s low serum IGF-1 and poor PWG and the risk of developing more severe ROP.…”
Section: Discussionsupporting
confidence: 86%
“…This is due to the fact that the missed treatable cases in our cohort had higher WG than the proposed cutoffs used in the Alex-ROP and Hg Alex-ROP algorithms. 36 The main strength of our study is that it is, to our knowledge, the first study wherein an algorithm was tailored to our population. Additionally, we compared our results to those of the currently widely available algorithms established in the same cohort of infants at a specific time, which yielded a fair comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main goals of the G‐ROP study was to reduce the number of infants screened by increasing specificity, and in this study, the number of infants requiring examination was reduced by 30.3% (Binenbaum et al., 2018). In validation studies from countries with different socio‐economic levels, a decrease between 14.1% and 50.0% was determined in the number of babies requiring screening (Ahmed et al., 2022; Binenbaum et al., 2020; Caruggi et al., 2021; Huang et al., 2022; Lu et al., 2023; Okbay Gunes et al., 2022; Raffa et al., 2023; Shiraki et al., 2019; Trinavarat et al., 2023; Vinayahalingam et al., 2022; Wadley et al., 2020; Yabas Kiziloglu et al., 2020) (Table 2). Similarly, in our study, there was a 19.8% decrease in the number of babies requiring screening.…”
Section: Discussionmentioning
confidence: 99%